Preparation of Magnetic Coal-measure Kaolinite Nanomaterials and Adsorption of Cr(Ⅵ) - Yuqi ZHAO; Suling YAO; Xianshu DONG; Ruifeng GUO; Yuping FAN (Kuangchan zonghe liyong)
This is an article in the field of mineral materials. In order to develop the high-value utilization technology of coal associated mineral resources kaolinite, coal-measure kaolinite nanomaterials(CKN) were prepared by indirect intercalation-liquid phase exfoliation method using coal gangue/slime, which is a solid waste product from washing, as raw materials. On this basis, the magnetic coal-measure kaolinite nanomaterials (MCKN) were prepared by chemical precipitation method, and the physical and chemical properties of MCKN were analyzed by XRD, SEM, BET, etc, and the different quality the ratio (m(Fe3O4)：m(CKN)=1: 3, 1: 4, 1: 5, 1: 6, 1: 7) MCKN adsorption of Cr (Ⅵ) behavior was discussed. The results show that MCKN with a mass ratio of Fe3O4 to CKN of 1:5 has the best adsorption effect on Cr(Ⅵ), MCKN has a good magnetic separation effect, and the adsorption rate of Cr(Ⅵ) can still be maintained after the fifth adsorption and desorption above 87%. CKN has a relatively complete morphology, a smooth surface, and a multilayer structure, some of which form nanotube structures, but some of them still exist in sheet-like structures. After loading Fe3O4, the surface of MCKN becomes rough, with an obvious 30～40 nm granular coating, indicating the successful preparation of MCKN, and the specific surface area of MCKN is higher than that of coal- measure kaolinite, while the specific surface area of MCKN is about twice that of CKN. The adsorption of Cr(Ⅵ) by MCKN conforms to the quasi-second-order kinetics, the model is chemical adsorption. The adsorption isotherm conforms to the Langmuir model, the saturated adsorption capacity is 17.26 mg/g, and the adsorption is an endothermic spontaneous process. In summary, the coal-measure kaolinite MCKN has good adsorption performance of Cr(VI), and is convenient for magnetic recovery and reuse, and can be used as a potential material for waste treatment in industrial applications.